ANALISIS PENGARUH GAYA KEPEMIMPINAN, LINGKUNGAN KERJA, DAN KOMITMEN TERHADAP DISIPLIN KERJA - Foudy Andres Rindengan; Agus Budi Purwanto (Sekolah Tinggi Ilmu Ekonomi YPPI Rembang, 2019)
This research was conducted at PT. Bangga Teknologi Indonesia area of Semarang which aims to find out: 1)Effect of Leadership Style on Work Discipline. 2) Effect of Work Environment on Work Discipline. 3) Influence ofCommitment to Work Discipline. 4) Effect of Leadership Style, Work Environment, and Commitment to WorkDiscipline. This type of research uses quantitative descriptive. Data collection techniques are done by distributingquestionnaires. The population in this study is the promoter of PT. Bangga Teknologi Indonesian with a sample of47 respondents and taken with Saturated Sampling techniques. The data analysis technique used is multiple linearregression analysis, t test, F test and R2 test. The results of the regression analysis test obtained the equation Y =11,494 + 0,085X1 + 0,605X2 + 0,780X3. This equation shows that the Work Discipline is influenced by LeadershipStyle, Work Environment, and Commitment. Based on the results of t test: 1) Leadership Style has a positive effecton Work Discipline. This is evidenced by t count > t table or 2.051> 1.680 and a significance value of 0.006 < 0.05,it can be concluded that Ho is rejected and Ha is accepted. 2) Work Environment has a positive effect on WorkDiscipline. This is evidenced by t count > t table or 2.351 > 1.680 and a significance value of 0.027 < 0.05, it can beconcluded that Ho is rejected and Ha is accepted. 3) Commitments have a positive effect on Work Discipline. Thisis evidenced by t count > t table or 3.229 > 1.680 and a significance value of 0.002 < 0.05, it can be concluded thatHo is rejected and Ha is accepted. 4) Leadership Style, Work Environment, and Commitment simultaneously orjointly influence the Work Discipline. This is evidenced based on the results of the F test that F-count > F-table is24,097 > 2,80 with a significance value of 0,000 < 0,05.